Identification of the enzymatic reactions encoded by the purG and purI genes of Escherichia coli. - Houlberg, U (1983)
The chromosomal locations of the genes purG and purI on the Escherichia coli linkage map are the opposites of those of Salmonella typhimurium. By methods which permit the identification of lesions in any of the five early enzymes of the purine de novo pathway, the gene-enzyme relationships of the purG and purI loci have been reevaluated in these two organisms. The results demonstrate that the relative locations of the genes encoding the two enzymes (phosphoribosylformylglycinamidine synthetase and phosphoribosylaminoimidazole synthetase) are similar in the two organisms. The gene products have been correctly determined in S. typhimurium. The gene products currently listed for the loci in E. coli are incorrect. The E. coli purG locus is equivalent to the S. typhimurium purI locus, and the E. coli purI locus is equivalent to the S. typhimurium purG locus.